EVALUATION OF THE INTERNATIONAL SITUATION Has the worst of the crisis happened? - Herrera García, Beatriz (2009)
Commodity prices have become increasingly volatile. The crisis has already had a severeimpact on global commodity markets with far reaching implications for the prospects of the developing world at large. Commodity price have been highly volatile during 2008. Most prices surged in the first half of 2008, continuing a trend that had began in 2003. Trends in world market prices reversed sharply from mid 2008; however, E.g., oil prices have plummeted by more than 60 per cent from their peak levels. The prices of other commodities also declined significantly. In the outlook, most of these prices are expected to even out further along with the moderation in global demand.